2020
DOI: 10.1002/cam4.3255
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative ultrasound radiomics in predicting response to neoadjuvant chemotherapy in patients with locally advanced breast cancer: Results from multi‐institutional study

Abstract: Background This study was conducted in order to develop a model for predicting response to neoadjuvant chemotherapy (NAC) in patients with locally advanced breast cancer (LABC) using pretreatment quantitative ultrasound (QUS) radiomics. Methods This was a multicenter study involving four sites across North America, and appropriate approval was obtained from the individual ethics committees. Eighty‐two patients with LABC were included for final analysis. Primary tumors w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 30 publications
3
55
0
Order By: Relevance
“…In addition, we also implemented stricter data inclusion criteria that result in the exclusion of US RF data from a single site. Although, the best selected features in this study do not demonstrate p < 0.05 statistical significant differences when assessed individually as in [ 54 ], a combination of some of discriminating features still resulted in a multi-feature classification model that predict a priori response to NAC with 88% sensitivity, 78% specificity, 84% accuracy, and 0.86 AUC. In contrast to the results in [ 54 ] where the best classification algorithm was the instance-based nearest neighbours, here the SVM-RBF results in the best response prediction model by combining features from both tumour core and tumour margin.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…In addition, we also implemented stricter data inclusion criteria that result in the exclusion of US RF data from a single site. Although, the best selected features in this study do not demonstrate p < 0.05 statistical significant differences when assessed individually as in [ 54 ], a combination of some of discriminating features still resulted in a multi-feature classification model that predict a priori response to NAC with 88% sensitivity, 78% specificity, 84% accuracy, and 0.86 AUC. In contrast to the results in [ 54 ] where the best classification algorithm was the instance-based nearest neighbours, here the SVM-RBF results in the best response prediction model by combining features from both tumour core and tumour margin.…”
Section: Discussionmentioning
confidence: 78%
“…This permits for the development of a priori response predictive model based on those features, as demonstrated herein. Recently, DiCenzo et al also reported a multi-institution response predictive model utilizing mean-values and texture features of QUS spectral parametric images from the tumour core [ 54 ]. In that study, the best response predictive results of 91% sensitivity, 83% specificity, 87% accuracy, and 0.73 AUC were attained [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The critical premise of quantitative ultrasound (QUS) is the processing of raw RF data from tissue backscatters, which can be used to characterize and distinguish phenotypic changes within a region of interest at a cellular level [12]. In preclinical studies, QUS had demonstrated efficacy in detecting treatment effects of various forms of cancer therapies [13][14][15][16][17]. QUS is sensitive to cell death-related structural changes even within 24 h, or clinically week 1 of treatment, arising from the changes in ultrasound scatterer elastic properties with phenomena like nuclear condensation, fragmentation, and the formation of apoptotic bodies.…”
Section: Introductionmentioning
confidence: 99%
“…Texture analysis from spectral images using gray level co-occurrence matrix (GLCM) can extract second-order imaging features like contrast (CON), correlation (COR), energy (ENE), and homogeneity (HOM), which can provide insights into different aspects of tumour heterogeneity. Studies have demonstrated the clinical e cacy of QUS in predicting response to neoadjuvant chemotherapy (NAC) in LABC [16][17][18][19][20] , and in patients with head-neck malignancies treated with radiotherapy 21 .…”
Section: Introductionmentioning
confidence: 99%